2004
DOI: 10.1103/physrevb.69.134113
|View full text |Cite
|
Sign up to set email alerts
|

Influence of magnetic on ferroelectric ordering inLuMnO3

Abstract: We have studied the influence of antiferromagnetic ordering on the local dielectric moments of the MnO5 and LuO7 polyhedra by measuring neutron powder diffraction patterns of LuMnO3 at temperatures near TN . We show that the coupling is weak, because the magnetic exchange coupling is predominantly in the ab plane of the MnO5 trigonal bipyramids, and the electric dipole moments, originating in the LuO7 polyhedra, are oriented along the hexagonal c axis. Anomalies in the dielectric properties near TN are thus ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 27 publications
(65 reference statements)
1
36
0
Order By: Relevance
“…The origin of the structural distortions in the magnetically ordered phase was suggested to lie in the displacements of the Mn 3+ ions from their = 1/3 ideal position in the unit cell. Interestingly, the deviation from = 1/3 is opposite for YMnO 3 ( increases below ) and LuMnO 3 ( decreases below ) [137,182]. As pointed out by Fabrèges et al [130], the deviation from = 1/3 determines the sign of the magnetic coupling between Mn 3+ spins in adjacent planes and the magnetic structure for different RMnO 3 .…”
Section: +mentioning
confidence: 85%
See 1 more Smart Citation
“…The origin of the structural distortions in the magnetically ordered phase was suggested to lie in the displacements of the Mn 3+ ions from their = 1/3 ideal position in the unit cell. Interestingly, the deviation from = 1/3 is opposite for YMnO 3 ( increases below ) and LuMnO 3 ( decreases below ) [137,182]. As pointed out by Fabrèges et al [130], the deviation from = 1/3 determines the sign of the magnetic coupling between Mn 3+ spins in adjacent planes and the magnetic structure for different RMnO 3 .…”
Section: +mentioning
confidence: 85%
“…Interestingly, the -axis of LuMnO 3 experiences a sizable increase with decreasing temperature below 200 K, signaling the onset of magnetic fluctuations [137,176,182]. This increase and the related anomaly in YMnO 3 (also in HoMnO 3 ) show that the buckling of the MnO 5 units and the related ferroelectric distortion discussed above are not the only mechanism affecting the thermal expansion behavior of the -axis.…”
Section: +mentioning
confidence: 95%
“…In these MFs, the FE order breaks the spatial inversion symmetry, whereas the magnetic order breaks the time-reversal symmetry. Owing to this separation, the ME coupling is weak in type I MFs [49]. The main effort is concentrated on improving the ME coupling in these MF materials.…”
Section: (I) Split-order Multi-ferroics (Type I)mentioning
confidence: 99%
“…Early reports indicated that the magneto-elastic coupling is particularly weak at T N ∼100 K in LuMnO 3 , the compound of interest in this study, because the magnetic coupling is predominantly in the ab-plane of the MnO 5 bipyramids while the electric dipole moments originating from the LuO 7 polyhedra are oriented along the c-axis 9 . Meanwhile, previous results from neutron diffraction measurements on a series of hexagonal manganites, AMnO 3 (with A = Lu, Y, and Lu 0.5 Y 0.5 ), suggested a possible isostructural transition at T N , with unusually strong magneto-elastic coupling involving Mn 10 .…”
mentioning
confidence: 99%